Evaluation of forage oat cultivars for alpine saline-alkaline environments: Trade-offs between yield, quality and stability - Yangji Jia; Haiying Zhang; Fengjuan Xue; Hao Sun; Xiaoli Wei; Xiaojian Pu; Yuanyuan Zhao; Chengti Xu (PLoS ONE, 2026)
Oat cultivation in the alpine saline-alkaline Qaidam Basin requires cultivars that balance yield, quality, and stability. Identifying suitable cultivars is key to sustainable forage production. Three oat cultivars (‘Qinghai 444’, ‘Qingtian No. 1', and ‘Zhengshi No. 1’) were evaluated in a two-year (2024 and 2025) field trial. We measured agronomic traits, yield, photosynthetic parameters, and forage quality. Mixed linear models, correlation analysis, and principal component analysis (PCA) were used to assess genotypic effects, environmental stability, and trait relationships. Cultivars exhibited distinct strategies. ‘Zhengshi No. 1’ achieved the highest fresh yield (3.29 and 1.96 t/ha) linked to greater stem diameter and photosynthetic rates but with high environmental sensitivity. ‘Qingtian No. 1’ provided stable, superior forage quality (highest crude protein: 11.44% and 10.33%). ‘Qinghai 444’ showed the most stable agronomic performance and highest water-use efficiency. Key trade-offs were identified, including a negative correlation between yield-related traits and forage quality (Relative Feed Value). The choice of optimal cultivar depends on primary goals: ‘Zhengshi No. 1’ for maximum biomass, ‘Qingtian No. 1’ for high quality, and ‘Qinghai 444’ for reliable performance under variable conditions. This provides an actionable framework for cultivar selection in saline-alkaline regions.